2004
DOI: 10.1002/ijc.20143
|View full text |Cite
|
Sign up to set email alerts
|

Mammography benefit in the Canadian National Breast Screening Study‐2: A model evaluation

Abstract: The CNBSS-2 among women aged 50 -59 did not show any significant difference in breast cancer mortality between a control arm screened annually by CBE and a study arm screened by CBE and mammography. Because of this design, the benefit of screening compared to no screening could not be evaluated. We therefore conducted a modeling effort to estimate the benefit of mammography or CBE compared to no screening. We incorporated demographic, epidemiologic and screening characteristics of the CNBSS-2 in MISCAN. Stage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 16 publications
0
24
1
Order By: Relevance
“…Mammography with cbe and bse detected cancers at an earlier stage than did cbe with bse, but no mortality benefit in women 50-59 years of age was observed 6 . A study by Rijnsburger et al 30 showed that cbe with bse should lower breast cancer mortality by 20% in women 50-59 years of age, but no adjustment was made for hormonal therapy and chemotherapy. In the province of Quebec, breast cancer screening with mammography has been offered to women 50-69 years of age since 1998, and that initiative could explain why our study shows that mammograms were more frequently positive in that age group.…”
Section: Figurementioning
confidence: 99%
“…Mammography with cbe and bse detected cancers at an earlier stage than did cbe with bse, but no mortality benefit in women 50-59 years of age was observed 6 . A study by Rijnsburger et al 30 showed that cbe with bse should lower breast cancer mortality by 20% in women 50-59 years of age, but no adjustment was made for hormonal therapy and chemotherapy. In the province of Quebec, breast cancer screening with mammography has been offered to women 50-69 years of age since 1998, and that initiative could explain why our study shows that mammograms were more frequently positive in that age group.…”
Section: Figurementioning
confidence: 99%
“…In fact some of the earliest evidence regarding combining various screening modalities come from the breast screening trial set within the Health Insurance Plan of New York where mammography was combined with CBE and almost 70% effect was estimated to be due to CBE [64] . The Canadian Breast Screening Study among women aged 50-59 (CNBSS 2) found no benefit from adding mammography to CBE and BSE [65] , with around 20% mortality reduction achieved due to CBE and BSE [66] . The evidence regarding the usefulness of BSE is more indirect, with evidence observed in CNBSS 2 [66] .…”
Section: Status Of Cbe and Bse In Lmicsmentioning
confidence: 99%
“…MISCAN is a well-validated microsimulation model used to evaluate various screening programs (21)(22)(23)(24). In MISCAN, individual life histories are simulated.…”
Section: Miscan Modelmentioning
confidence: 99%
“…Mammographic sensitivities for premenopausal women (under 50 years) and MRI sensitivities were first estimated from the (largest) MRISC study. Stage-specific sensitivities of CBE in women 55 years or older were based on the Canadian National Breast Screening study (23). For women under 50 years, the CBE sensitivity was assumed to be 50% of the sensitivity for women >55 years.…”
Section: Application Of the Modelmentioning
confidence: 99%